Bahasa indonesia PERANAN PERILAKU DAN DUKUNGAN TOKOH MASYARAKAT TERHADAP KEPEMILIKAN JAMBAN SEHAT DI TANJUNGPINANG - Samosir, Kholilah (UPPM Politeknik Kesehatan Kemenkes Ternate, Maluku Utara, Indonesia, 2019)
The problem of sanitation development in Indonesia is the problem of socio-cultural challenges, one of which is the behavior of residents  who are accustomed to defecating  in the vain places, The purpose of this study was to find out the Role between Behavior, Habits and Support from Community Figure on  the ownership of the healthy latrines in the Coast Village of Bugis, Tanjungpinang City. This study included analytic observational research and the design used was cross sectional, namely to study the dynamics of correlation between the risk factors and the effects, by approaching, observing or collecting data at the same time. The populations is this study were 372 householder of the coast Village of Bugis with a sample of 193 that were householder. The results of the study indicated that there is a role  between Habits (ρ = 0,000). There is no role between Knowledge (ρ = 0,788), Attitude (ρ = 0,092) and  Support from Community Figure  (ρ = 1,000) on  the ownership of the healthy latrines. The recomendation given in this study is that all relevant parties shald support the Community of  Bugis Village to have healthy latrines that meet requirements of health so that it is proper to use . .